Agentic traits are associated with success in science more than communal traits. (1st February 2017) - Ramsey, Laura R.
Abstract: Previous research has demonstrated that men are stereotyped as agentic and women are stereotyped as communal. Therefore, perceived importance of agentic versus communal traits for success in science may contribute to subtle gender biases in science. Perceptions of science faculty may be especially important to investigate due to their positions as role models, exemplars, and gatekeepers. The present study tested the hypothesis that agentic traits are considered more important for success in science than communal traits. Faculty ( n = 115) and undergraduate students ( n = 122) from science departments at large, research-intensive universities were surveyed using either an open- or closed-ended format, so as to gauge what traits come to mind as well as those possibly related to success in science. Both faculty and students, regardless of gender, perceived agentic traits as more important for success in science than communal traits. Additionally, there were no gender differences in self-perceptions of agentic traits, though women perceived themselves as more communal than men. Finally, participants' perceptions of their own traits correlated with those they perceived as necessary for success in science. Highlights: Survey of science faculty and students was conducted. Participants listed and/or rated which traits are important for success in science. In open-ended format, participants listed more agentic traits than communal traits. Participants rated agentic traits as more important for success in science.